Ações realizadas na atenção básica como componente da rede de cuidados à pessoa com deficiência - Silva, Jerssica Mayara Agustinho da (2023)
The Care Network for People with Disabilities concerns the promotion, inclusion and acceptance of people with disabilities, with guaranteed access and quality of services, offering under the interdisciplinary logic pointing to Basic Care. Objective: To analyze the actions carried out by the Primary Care Teams and the Expanded Family Health Center aimed at people with disabilities. Methodology: This is a descriptive, inferential, cross-sectional, multicenter study with a quantitative approach. The study was carried out in eight Brazilian states. Professionals from the primary care teams and the expanded family health center participated in this study. Results: The Expanded Family Health Center has more knowledge about the Network than the Primary Care teams, so both teams sometimes meet the needs and demands of this public as well as guide and carry out home monitoring. The study presents a lower prevalence for the Expanded Family Health Center in terms of specific Primary Care actions such as early identification of deficiencies through prenatal care, reception and risk classification. Conclusion: The actions carried out by the two teams promote and collaborate with patients in relation to the care network for people with disabilities.